Pronunciation Performance in English Monologues among Islamic Education Students: A case study at Islamic University of Jambi - Ramdhano, Yanri (EXCELLENCE: Journal of English and English Education, 2025)
This study investigates the English pronunciation performance of Islamic Education students at UIN Sulthan Thaha Saifuddin Jambi. Forty undergraduate students participated by submitting a 1–2 minute spoken monologue on the topic of “friendship.” Each performance was evaluated using a rubric adapted from the University of Colorado, assessing five pronunciation aspects: individual sounds, word stress and endings, intonation and rhythm, fluency and hesitation, and overall comprehensibility. The findings revealed that the overall mean score was low (1.32 out of 4), with the majority (80%) categorized as having “Ineffective” pronunciation. Word stress and endings posed the greatest challenge, while fluency had a slightly higher average. Only a few students demonstrated satisfactory pronunciation, marked by clearer articulation, better rhythm, and fewer hesitations. Qualitative observations supported these findings by identifying frequent errors in segmental and suprasegmental features. The results highlight an urgent need for explicit pronunciation instruction within the English curriculum of Islamic Education programs. The study recommends integrating phonetic training, pronunciation-focused tasks, and digital tools to improve learners’ speaking skills. Future research should explore the long-term development of pronunciation and the impact of targeted interventions.